Modulation of erythrocyte membrane mechanical stability by 2,3-diphosphoglycerate in the neonatal poikilocytosis/elliptocytosis syndrome. - Mentzer, W C (1987)
To explain the transient anemia and poikilocytosis seen during infancy in hereditary elliptocytosis (HE), we resealed erythrocyte (RBC) ghosts from affected children or their elliptocytic parents with 2,3-diphosphoglycerate (DPG) (0-8 mM), a compound that dissociates membrane skeletons, then measured ghost mechanical stability in the ektacytometer. Without added 2,3-DPG, ghost mechanical stability was subnormal in infantile poikilocytosis (IP) and HE but was even more abnormal in hereditary pyropoikilocytosis (HPP). Addition of 2,3-DPG (2.55 mM) to IP or HE ghosts, decreased their stability to that of HPP ghosts (without 2,3-DPG). Nonphysiological 2,3-DPG levels (6-8 mM) were required to elicit a similar effect in normal ghosts. The data suggest that free 2,3-DPG, present in neonatal RBC as a consequence of diminished binding to HbF, may render HE susceptible to in vivo fragmentation. The developmental switch from fetal to adult hemoglobin, by diminishing available free 2,3-DPG, may explain the abatement of poikilocytosis and hemolytic anemia that accompanies maturation.